Debating austerity in Ireland crisis, experience and recovery - Moore-Cherry, Niamh; McHale, John; Heffernan, Emma (Royal Irish Academy, 2017)
The austerity that followed the recent economic and financial crisis in has led to impassioned debates across the social sciences and the public at large. Although Ireland was not its only victim, the depth of the interacting economic, banking and budgetary crises has meant that the level of public interest has been especially intense. Among the hotly debated questions: what is austerity? Was it necessary? What have been its consequences? One of the defining features of the debate to date has been its tendency to polarise opinion and adopt a one-dimensional perspective. This book challenges us to adopt a more nuanced approach to understandings of austerity, and by extension the path to recovery. The book brings together leading national and international experts from across the social sciences to debate this traumatic period in Ireland's economic and social development. The papers were selected from a conference at the Royal Irish Academy, peer-reviewed and rewritten with the addition of a substantial introduction and conclusion by the editors.